2006
DOI: 10.1214/00911790500000710
|View full text |Cite
|
Sign up to set email alerts
|

On the maximum queue length in the supermarket model

Abstract: There are $n$ queues, each with a single server. Customers arrive in a Poisson process at rate $\lambda n$, where $0<\lambda<1$. Upon arrival each customer selects $d\geq2$ servers uniformly at random, and joins the queue at a least-loaded server among those chosen. Service times are independent exponentially distributed random variables with mean 1. We show that the system is rapidly mixing, and then investigate the maximum length of a queue in the equilibrium distribution. We prove that with probability tend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
141
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 15 publications
4
141
0
Order By: Relevance
“…Its path space evolution was studied by Graham [11] who moreover showed that, starting from independent initial states, as N → ∞, the queues of the limiting process evolve independently. Luczak and McDiarmid [15] showed that the length of the longest queue scales as (log log N )/ log D + O (1). Certain generalizations have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Its path space evolution was studied by Graham [11] who moreover showed that, starting from independent initial states, as N → ∞, the queues of the limiting process evolve independently. Luczak and McDiarmid [15] showed that the length of the longest queue scales as (log log N )/ log D + O (1). Certain generalizations have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the feedback cost, and yet to keep the delay 'small', JSQ has been generalized to SQ(d), whereby the dispatcher runs JSQ only for a subset of d randomly sampled servers from the uniform distribution (see Mitzenmacher [5] and Luczak and McDiarid [3]). Note that SQ(d) reduces to a simple uniform random selection when d = 1, and to JSQ when d = N , where N is the total number of servers.…”
Section: Introductionmentioning
confidence: 99%
“…If there is more than one chosen server with a shortest queue, then the customer goes to the first such queue in her list of d. Service times are independent unit mean exponentials, and customers are served according to the first-come first-served discipline. Recent work on the supermarket model includes [5,6,7,14,16,17,25]. The survey [22] gives several applications and related results.…”
Section: Introductionmentioning
confidence: 99%
“…Further, again for a fixed positive integer k 0 , as n tends to infinity, in the equilibrium distribution the proportion of queues with length at least k 0 converges in probability to λ (d k 0 −1)/(d−1) , and thus the probability that a given queue has length at least k 0 also converges to λ (d k 0 −1)/(d−1) . Recent results in [16] include rapid mixing and two-point concentration for the maximum queue length in equilibrium. The main contribution of the present paper is to give quantitative versions of the convergence results for the supermarket model mentioned above, and to extend them to hold uniformly over all times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation